Corrigendum to “Highly sensitive, selective, and rapid response colorimetric chemosensor for naked eye detection of hydrogen sulfide gas under versatile conditions: Solution, thin-film, and wearable fabric” [Sens. Actuators B: Chem. 341 (2021) 130013] (Sensors and Actuators: B. Chemical (2021) 341, (S0925400521005827), (10.1016/j.snb.2021.130013)) - Zheng, Jian; Noh, Ha Lim; Chun, Hye W.; Oh, Byeong M.; Lee, Junyeop; Choi, Sang Kee; Kim, Eunha; Jung, Daewoong; Lee, Woo Sung; Kim, Jong H. (Sensors and Actuators B: Chemical, 2022)
The authors regret to inform that the article included typo in affiliation of Jian Zheng. The correct affiliation is as follows: “b. School of Chemistry and Chemical Engineering, Lingnan Normal University, Zhanjian, 524048, People's Republic of China.” The authors regret to inform that the article included typo in biography of Jian Zheng. The correct biography is as follows: "Jian Zheng is a lecturer in the School of Chemistry and Chemical Engineering, Lingnan Normal University at People's Republic of China. He received Ph.D degree from Guangzhou Institute of Chemistry at University of Chinese Academy of Sciences in 2016. He worked as a postdoctral research associate in Professor Jong H. Kim's group in Ajou University at Republic of Korea. His current research is focused on the synthesis of functional dyes for chemosensor applications."